KARAKTERISASI GEN β KETOACYL-ACP SYNTHASE II (KAS II) PADA Elaeis guineensis, Elaeis oleifera, DAN HIBRIDA INTERSPESIFIK - Heri Adriwan Siregar; Sri Wening; Abdul Razak Purba (Pusat Penelitian Kelapa Sawit, 2016)
Oil palm (Elaeis guineensis) is currently the highest edible oil-producing plant in the world. E. oleifera is another species of oil palm that is not widely cultivated due to lower productivity. Oil extracted from E. guineensis has a balance ratio of saturated to unsaturated fatty acids level, while E. oleifera has a higher unsaturated fatty acids. Long chain saturated fatty acids are more harmful for human health than unsaturated fatty acids. Gene encoding β-ketoacyl ACP synthase II (KAS II, EC 2.3.1.179) was studied, as this enzyme is responsible for biosynthesis of unsaturated fatty acids. Observation and analysis were conducted for KAS II gene and fatty acids content of E. guineensis represented by DxP Lame, DxP Langkat and CMR78 samples, E. oleifera represented by Suriname origin, and two hybrids (E. guineensis x E. oleifera (Brazil and Suriname)). The results showed E. oleifera Suriname had the highest concentration of oleic acid, followed by E. guineensis (CMR78). KAS II gene sequences alignment showed some genetic variation within E. guineensis and hybrids, while the high level of variation found between E. guineensis and E. oleifera was considered caused by species difference.